GDP growth and earnings management: Evidence from China - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2020)
Using data from China, we examine whether and how the incentive to boost GDP growth at the government level affects earnings management at the firm level. We find that firms in provinces with GDP growth lower than the national level or the average of the adjacent provinces are more likely to engage in earnings management than firms in other provinces. Specifically, they are more likely to inflate revenues, overproduce, and delay asset impairment losses. The aggregate earnings management induced by GDP growth incentives accounts for about 0.5% of GDP. The results are stronger for local state-owned enterprises, in provinces with a lower level of marketization, for firms in provinces with younger governors, and in the years immediately prior to the turnover of provincial officials. Overall, this paper provides systematic evidence on how firms engage in earnings management to boost the GDP growth in their provinces.